1999
DOI: 10.1143/jjap.38.l1466
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Negative-Ion-Assisted Silicon Oxidation by Radio-Frequency Bias

Abstract: We derive an improved prescription for the merging of matrix elements with parton showers, extending the CKKW approach. A flavour-dependent phase space separation criterion is proposed. We show that this new method preserves the logarithmic accuracy of the shower, and that the original proposal can be derived from it. One of the main requirements for the method is a truncated shower algorithm. We outline the corresponding Monte Carlo procedures and apply the new prescription to QCD jet production in e + e − co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…12 To create a region with low T e ͑suitable to generate SF 6 Ϫ and SF 5 Ϫ ) a magnetic filter made of permanent magnets was used. The filter divided the plasma into the so-called source plasma ͑SPL͒ and target plasma ͑TPL͒.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…12 To create a region with low T e ͑suitable to generate SF 6 Ϫ and SF 5 Ϫ ) a magnetic filter made of permanent magnets was used. The filter divided the plasma into the so-called source plasma ͑SPL͒ and target plasma ͑TPL͒.…”
Section: Resultsmentioning
confidence: 99%
“…The replacement of mobile electrons with heavy negative ions drastically changes the plasma behavior. Thus elaborate works concerning diagnostics techniques, [1][2][3][4] applications, 5,6 and theoretical investigations [7][8][9] have been published over the last years. Langmuir probes have often been used to diagnose the electronegative plasmas, due to their simplicity of construction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By attaching one electron, oxygen can become a negative oxygen (O − ) ion, which is an anion radical. Several reports have indicated that O − ions cause strong oxidation in comparison with positive oxygen ions [3]. A recent study on plasma processing using an oxygen plasma suggested that the O − ions may play a key role in proceeding oxidation [4].…”
mentioning
confidence: 99%